Level 1 Regional Trainer Training as an Effort to Increase the Competence of Taekwondo Coach’s in East Java - Slamet Junaidi; Puspodari; Dhedhy Yuliawan; Moh. Nur Kholis; M. Akbar Husein Allsabah; Sugito; Weda; M. Yanuar Rizki; M. Khoirul Akbar (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Coaching for beginner sportsmen is ussualy carried out by coaches who have basic level training knowledge, of course, their training abilities are very limited. The best coaches who have competence usually train senior athletes. It is truly ironic that even at a critical and sensitive age for the development of physical abilities, beginber sportsmen are handled by inadequate coaches. Actually training at the level of beginner athletes requires knowledgeable and skilled trainers so they can teach the right movements and provide examples of the right skill. Coaches who deal with athletes at a basic level should understand the pattern of growth and development of novice athletes. One way that must be done is to make improvements by building and implementing a long term athlete development system that allows coaching athletes from an early age by providing training that is appropriate to their lever of growth and development. Efforts to improve the competence of basic level taekwondo trainers through Level 1 Regional trainer training activities seek to encourage the need for reconstruction of coaching and achievement programs that do not only rely on the athlete’s side, but are also accompanied by the coach’s role and strategy in designing training programs for athletes effectively and on target. The purpose of this community service activity is to provide program output, namely the creation of quality coaches who have good competence and skills to coach athletes. Effort to improve the competence of basic level taekwondo trainers through the level 1 regional trainers training activities are expected to continue to become programs or agendas in academic forums that become spearheads for athlete achievement to transform the skills and competency needs of trainers